2020
DOI: 10.1136/bmjopen-2020-039367
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use patterns and attitudes in Singapore young male adults serving military national service: a qualitative study

Abstract: ObjectivesTo explore tobacco use patterns and factors influencing tobacco use in young Singaporean men serving military national service.MethodsA qualitative study using in-depth telephone interviews and maximum variation sampling was conducted with 29 Singaporean men who have completed their national service in 2017–2018. Data were analysed using thematic analysis.ResultsMore than half (51.7%) of the participants started smoking before age 18, with a mean age of smoking initiation at 16 years. At the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…[ 14 ] and Tan et al . [ 16 ] found that among ever tobacco users, majority reported tobacco product initiation before the age of 18 years. Similar pattern of early initiation of tobacco use was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] and Tan et al . [ 16 ] found that among ever tobacco users, majority reported tobacco product initiation before the age of 18 years. Similar pattern of early initiation of tobacco use was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%